MECHANICAL AND THERMAL PROPERTIES OF GRAPHENE OXIDE REINFORCED POLYPROPYLENE/PINEAPPLE LEAVES FIBRE COMPOSITES - Monisha Devi Muragan; Zainoha Zakaria; Azman Hassan (PERINTIS eJournal, 2021)
Polypropylene (PP) has many interesting properties and widely used in many applications. Natural fibres such as pineapple leaf fibre (PALF) have been used to improve the mechanical properties of PP due to various advantages such as low cost and low density. The objective of this study is to investigate the effect of graphene oxide (GO) content on mechanical and thermal stability of PP/PALF composites. The effect of PALF on mechanical and thermal properties of neat PP was also investigated. The PP/PALF and PP/PALF/GO composites compatibilized with polypropylene-grafted-maleic anhydride (PP-g-MAH) were melt-blended using co-rotating twin-screw extruder and injection moulded into test samples. Throughout the study, the weight ratio of PP: PALF: PP-g-MAH was fixed at 85:10:5 weight percent. PP/PALF/GO with different GO contents (0, 0.5, 1.0, 2.0 phr) were prepared. Mechanical properties of the polymer composites were studied through tensile and impact tests while thermal properties were investigated through thermogravimetric analysis (TGA). All mechanical properties with the exception of elongation break improved with the incorporation of 10 % PALF into PP. The addition of 1.0 phr GO increased the impact strength of PP/PALF from 44.85 to 49.49 J/m, which is about 10 % increase. However, the tensile strength and Young’s modulus did not significantly change with GO content. The study has demonstrated that simultaneous incorporation of GO and PALF into PP has enhanced the mechanical strength of PP. The thermal stability of PP/PALF/GO composites as indicated by Tmax at 0.5 phr GO content was significantly higher than neat PP and PP/PALF composites.